Genetic link with cholelithiasis among pediatric SCA Tunisian patients: Examples of UGT1A1, SLCO1A2 and SLCO1B1. Issue 2 (7th February 2016) - Chaouch, Leila; Kalail, Miniar; Darragi, Imen; Boudrigua, Imen; Chaouachi, Dorra; Ammar, Slim Ben; Mellouli, F.; Bjaoui, M.; Abbes, Salem
Abstract : Aims and background : Hyperbilirubinemia is often observed in chronic hemolysis and results in the formation of pigment cholelithiasis that could be increased by the presence of defected enzymes involved in the bilirubin metabolism. Indeed, this is the first report that interested in the study of polymorphisms in genes encoded for enzymes involved in the bilirubin metabolism: rs 4149056 of SLCO1B1 and rs4149000 of SLCO1A2 in combination with rs8175347 and rs887829 of UGT1A1 in order to find a correlation between the polymorphisms studied and the presence of gallstones in a population of sickle cell anemia (SCA) pediatric Tunisians. Material and methods : Our study involved 102 unrelated Tunisian subjects. All SCA patients are children (less than 16 years old) and were characterized by hyperbilirubinemia and 52 of them have cholelithiasis. The polymorphisms of the candidate genes were analyzed for all subjects by PCR/sequencing. Genotype and allele frequencies between cases and controls were compared using Pearson's chi-square test with a significance threshold of P < 0.05 (compare 2, version 1.02). Results : The novelty of this report is that children carrying the combined genotype of the rs studied: (TA7TA7)/TT/TC/GA have a higher risk to develop gallstones ( P = 0.0027, RR = 18.27 (20.0061–915.28)). Conclusion : Altogether our data provide the implication of UGT1A1 and SLCO1A2 in sickle cell anemia-related cholelithiasis.